Exploring the Impact of Self-Learning Campus Portals Using the Technology Acceptance Model - Elisa; Susilawati; Muhajirs; A. Halim; A. Farhan; Elmi Mahzum; A. Wahyuni (LPPM Undiksha, 2025)
The low utilization of campus portals as a means of independent learning by students, even though the portal has been provided as part of the digitalization efforts of higher education. Therefore, it is necessary to explore further how various variables in the Technology Acceptance Model (TAM), such as perceived ease of use, perceived usefulness, attitude toward use, and intention to use, influence the level of acceptance and utilization of campus portals for independent learning. The Independent Campus Portal uses the variables Perceived Ease of Use (PEU), Perceived Usefulness (PU), Attitude Toward Using (ATU), Behavioral Intention to Use (BIU), and Actual System Use (ASU) by applying the Technology Acceptance Model (TAM). Data collection for this study was carried out using a questionnaire. The sample used was 61 students majoring in Physics Education. The statistical testing methods used were statistical tests for normality, homogeneity, validity, reliability, and hypothesis testing using the t-test with the SPSS program. The results of this study indicate that of the six hypotheses proposed, all six hypotheses were accepted and had a significant influence. This research demonstrates the need for improved system optimization and technical support services to enable the portal to function more effectively and efficiently in supporting the Independent Campus program. The implications of this research demonstrate the importance of developing and optimizing the campus portal as a self-directed learning tool that is responsive to the needs and perceptions of users, particularly students.